ASUHAN KEBIDANAN PADA IBU NIFAS NY.R DENGAN HEMOGLOBIN (HB) RENDAH DI PMB SRI WIYANTI GRESIK - Mega Permata Sari; Fauziah F. Hernanto (Jurnal Medicare, 2026)
Postpartum maternal anemia is a condition in which the body's hemoglobin level is less than 10 g/dl. Although pregnant women have sufficient iron content, the concentration of prenatal hemoglobin is usually around 11 to 12 g/dL. Anemia can be exacerbated by reduced blood volume during delivery and respiratory periods. In 2020, postpartum maternal mortality from anemia reached 30% in Indonesia. The research sample used was 1 (one) mother fas with Anemia at PMB Sri Wiyanti Gresik. The method of continuity of care, which is continuous care, is used in running foster care. The solutions provided are KIE regarding nutritional needs in niphas, improvement of resting patterns and provision of Fe tablets. From the care provided, the results are that the difficulty can be handled properly so that it does not cause more dangerous effects.